AWARENESS OF UNIVERSITY UNDERGRADUATE STUDENTS ON GENETICALLY MODIFIED ORGANISMS IN GHANA - Yussif, A-S K.; Quansah, L. (UDS International Journal of Development, 2022)
Consumers are generally subjected to Genetically Modified (GM) food items either directly or indirectly through the consumption of processed foods produced using GM ingredients. After the introduction of the first commercial GM foods in the early 1990s, contentions arose with regard to the potential benefits and risks to human and environmental health. This cross-sectional descriptive study focused on the awareness and perceptions of students from two Ghanaian public universities namely, the Kwame Nkrumah University of Science and Technology in the Ashanti Region and the University for Development Studies in the Northern Region. A total of 304 students participated in the study. The data were analyzed using the statistical software SPSS (Version 20). The results showed a high level of Genetically Modified Organisms (GMOs) awareness among students in the two universities. The fundamental theories underpinning GMOs, biotechnology, and genetic modification were understood by students. Most students had their information about GMOs from the media. Age played a major role in perceptions as students in the age range 21-23 were more receptive to innovations compared to students >23 years. Students with programmes related to biological sciences had fewer reservations towards GMOs unlike students pursuing non-biological science fields. Â Keywords: Biotechnology, Genetically Modified Organism/Food, Students, Awareness, University